2008
DOI: 10.1373/clinchem.2007.089953
|View full text |Cite
|
Sign up to set email alerts
|

Association of Changes in Oxidative and Proinflammatory States with Changes in Vascular Function after a Lifestyle Modification Trial Among Obese Children

Abstract: Background: The association of changes in oxidative and proinflammatory states with vascular function after diet and exercise intervention among obese children has not been previously explored. Methods: In this 6-week diet and exercise intervention study in 35 obese children, age 12 to 18 years, we evaluated the relationship between changes in anthropometric indices, measures of insulin resistance, C-reactive protein (CRP), oxidized LDL (ox-LDL), and oxidative stress markers with changes in caro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
94
1
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(102 citation statements)
references
References 37 publications
(40 reference statements)
3
94
1
1
Order By: Relevance
“…2 Indeed, recent studies showed a positive relationship between obesity, inflammatory C-reactive protein, 3 and oxidized low-density lipoprotein (ox-LDL). 4,5 Moreover, we showed that ox-LDL was associated with the incidence of the metabolic syndrome 6 and with several metabolic syndrome components, especially visceral obesity. 7,8 Stevioside was found to exert antihyperglycemic and insulinotropic effects in a non-obese animal model of type 2 diabetes 9 by acting directly on pancreatic cells.…”
Section: Introductionmentioning
confidence: 93%
“…2 Indeed, recent studies showed a positive relationship between obesity, inflammatory C-reactive protein, 3 and oxidized low-density lipoprotein (ox-LDL). 4,5 Moreover, we showed that ox-LDL was associated with the incidence of the metabolic syndrome 6 and with several metabolic syndrome components, especially visceral obesity. 7,8 Stevioside was found to exert antihyperglycemic and insulinotropic effects in a non-obese animal model of type 2 diabetes 9 by acting directly on pancreatic cells.…”
Section: Introductionmentioning
confidence: 93%
“…For example, exercise training lowered sRBP-4 concentrations in adults and overweight children, correlating with improved insulin sensitivity and lower CRP and IL-6 (58 ). Lifestyle modification in obese children reduced CRP and MDA concentrations, correlating with improvements in endothelial function (84 ). Among older adults, 6 months of resistance training improved oxidative stress, assessed by measurement of exercisedinduced lipid hydroperoxides (85 ).…”
Section: Exercisementioning
confidence: 98%
“…Blood samples collected during the study (preingestion and 2-h postingestion) were analyzed for norepinephrine (HPLC), oxidized LDL (ELISA, Mercodia, Uppsala Sweden), glucose (EIA), and insulin (chemiluminescent assay). This was done as these markers, or systems they provide insight into, may be have been influenced by our intervention and can influence endothelium-dependent vasodilation (2,5,26,28). Additionally, we also measured serum total epicatechin to document the effect of cocoa ingestion (preingestion, 1-h postingestion, and 2-h postingestion).…”
Section: Measurementsmentioning
confidence: 99%